Reflexões sobre formação de professores - Moreira, Hélen Fernandes (2021)
The theme of this thesis, which investigates the need for the rupture of the traditional paradigms for the emerging, meets the needs of this research, aiming to collaborate in the search for the improvement of the education to the future. The paradigmatic concepts, although defined by several theorists (Khun, Morin, Moraes, Behrens, Capra, among others) converge to reflect on the transitions in the field of changes that occur in the development of science. We maintain that education must be understood as a social process, being multidimensional, innovative, creative and opening to dialogue. Therefore, the training of university professors must be guided by the self referential process, in (trans) form (action) and retroaction in relation to events and planetary consciousness. We believe that teacher training needs to be built by its identity in professional and personal performance through the ecology of knowledge (Boaventura Santos,1998). We affirm Morin's maxim regarding to the complexity to the world education and the complex thinking: for the author “complexity is a problem word and not a solution word” (Morin, 2008). The Epistemology of Complexity served us as a study in the training of university professors based on complex thinking, based on the works of Edgar Morin. Education for the 21st century seeks a new era: the conception of self-knowledge, based on the assumption that it is a continuous reconstruction and it is fundamental to understand the Seven Necessary Knowledge for the Education of the Future: The blindness of knowledge: error and illusion; the principles of relevant knowledge; teach the human condition; teach earthly identity, face uncertainties; teach the understanding and ethics of the human race (Morin), as a sine qua non condition for living. In view of the statements presented, this thesis has as its generais objective the reflection and analysis of the promotion of the Reform of Thought and the study of its possibility for the training of university teachers. We also point out as specific objectives: the understanding and analysis of the concepts of complexity and transdisciplinarity (Fazenda, Japiassú, Suanno). We also emphasize the possible contributions of the Creative Schools and the Ecoformadores Creative Projects (ZWIEREWICZ).